WHEN FANS AND HATERS ARE ON THE SAME BOAT: A DECONSTRUCTIVE READING OF BOWO AND TIK TOK - Pepen Priyawan; Alisya Rusdianti; Adinda Nurfauziah; Asmarani Asmarani (Fakultas Komunikasi, Sastra, dan Bahasa, 2019)
This study analyses the viral impact of Bowo, a teenage celebrity from TikTok (a socialmedia site) as well as comments from netizens who happened to be Bowo’s fans orhaters. In addition, the study used theories of cultural studies from Derrida, Adorno andHorkheimer to analyze the entertainment industry as well as netizens, both fans andhaters of Bowo. The role and judgments of fans and haters of Bowo will be shown to seethe paradoxes and parallel of this phenomenon. Thus, the study applied a descriptivequalitative method to analyze data. The results indicate that although netizens know thatwhat they see in TikTok may be fabricated, some netizens still felt deceived by Bowo’sappearances in TikTok. Those feelings were shown in their comments in social media. Inaddition to feeling deceived, the results show how female teenagers who engaged inonline discussions regarding Bowo seemed torn into adoring and abhorring Bowo.